Evaluation of Antipsoriatic Effect of Ivermectin in Animal model of Psoriasis - Salim Mahmood, Ahmed; Zeena Ayad Hussein; Nabaa Mohammed Ibrahim (Iraqi Journal of Pharmaceutical Sciences, 2025)
Ivermectin (IVR) is widely used for the treatment of onchocerciasis and other nematode infections .Recent studies have reported that IVR has an anti-inflammatory effect and is used in the treatment of allergic asthma, dermatitis, and arthritis. Psoriasis is a chronic immune-mediated inflammatory skin disease in which IL-17 and VEGF play an important role as pro-inflammatory and angiogenic mediators.To evaluate the therapeutic effect of IVR in psoriasis, we used an imiquimod (IMQ)-induced psoriasis model in rats. Twenty-four male wister-albino rats, age 3-4 monthe and weighing 170-200 g were used in this experiment. They were assigned at random into four groups, each group include 6 animals. Rats in each group (except normal control group) are topically administered 62.5 mg of IMQ cream for 10 days, then they were treated for 12 days with one of the following drugs starting from the day four after first application of IMQ cream: the first group treated with subcutaneous (SC) injection of normal saline once daily and consider as positive control group; the second one is Methotrexate (MTX) treated group using conventional dose in autoimmune disease (1.0 mg/kg/week, intraperitoneal injection); and last group is IVR treated group (0.5 mg/kg/day, SC injection). Subcutaneous administration of IVR to the rats, significantly minimize the Psoriasis Area Severity index (PASI) regarding the thickness, scaling and erythema (3.00 ± 2.19) comparing to the positive control group (6.83 ± 1.16) with p value < 0.05. Furthermore, IVR attenuate the histopathological changes of skin lesion with no significant differences comparing to MTX treated group (standard drug for psoriasis treatment). In addition to that, the level of IL-17 and VEGF in psoriatic skin lesion were significantly reduced by IVR and MTX compared to a positive control group (p < 0.05), suggesting the ability of this drug in the alleviation of psoriasis by this mechanism.